Pathogenesis from the microbial-gut-brain axis in white matter injury in preterm infants: A review - Wang, Yuqian; Zhu, Jing; Zou, Ning; Zhang, Li; Wang, Yingjie; Zhang, Mengmeng; Wang, Chan; Yang, Liu (Frontiers in Integrative Neuroscience, 2023)
White matter injury (WMI) in premature infants is a unique form of brain injury and a common cause of chronic nervous system conditions such as cerebral palsy and neurobehavioral disorders. Very preterm infants who survive are at high risk of WMI. With developing research regarding the pathogenesis of premature WMI, the role of gut microbiota has attracted increasing attention in this field. As premature infants are a special group, early microbial colonization of the microbiome can affect brain development, and microbiome optimization can improve outcomes regarding nervous system development. As an important communication medium between the gut and the nervous system, intestinal microbes form a microbial-gut-brain axis. This axis affects the occurrence of WMI in premature infants via the metabolites produced by intestinal microorganisms, while also regulating cytokines and mediating oxidative stress. At the same time, deficiencies in the microbiota and their metabolites may exacerbate WMI in premature infants. This confers promise for probiotics and prebiotics as treatments for improving neurodevelopmental outcomes. Therefore, this review attempted to elucidate the potential mechanisms behind the communication of gut bacteria and the immature brain through the gut-brain axis, so as to provide a reference for further prevention and treatment of premature WMI.